Evidence-Based Psoriasis Diagnosis and Treatment (Updates in Clinical Dermatology,, 2018)
Given the multitude of new treatment options for psoriasis, including topicals, phototherapy, oral systemic therapy, and injectable biologics, the treatment of the disease has truly become an art. Evidence-Based Psoriasis passes on this art to practicing physicians in a very practical and easy-to-use format, focusing on mild, moderate, and severe psoriasis. Offering evidence-based information in a concise text, this book discusses new treatment options, including topicals, phototherapy, oral systemic therapy, and injectable biolgoics. This text also describes unique methods of use, such as sequential and combination therapy, and is written for practicing dermatologists, residents, and primary care physicians. Evidence-Based Psoriasis also includes high quality color photographs and tables for quick and easy reference.